Urban public space as social interaction space: case study in Petaling Street - Ab Rahman, Syakir Amir; Azizan, Ainina; Zahari, Rustam Khairi; Asmawi, M. Zainora (Global Academic Excellence (GAE), 2020)
Despite the fading cultural value as a Chinatown, the relationship of the society and its public space is a form of a natural phenomenon that is inseparable. The changing functions of public space in Malaysia were identified to decrease the quality of social and cultural activities in Petaling Street. Therefore, this study aims to explore urban public spaces as the main social driver in crating interaction in Petaling Street, Kuala Lumpur. The relationship between attributes of the urban public space and visitor retention were analyzed in this study. In terms of social interaction, the user activities were interrelated with the sociability of the urban space. The questionnaire survey was selected as the main medium for data collection distributed to the visitors and locals within the Klang Valley who have visited Petaling Street Chinatown. A total of 150 respondents involved and the analysis shows that street furniture does affect their preferences in an urban public space. Furthermore, the time spent by respondents will increase depending on the external factors such as weather and aesthetics. On the other hand, the internal factor that contributes to the number of visitors in Petaling Street Chinatown is their accompanying traveler which in the context of a solo traveler, the street should be celebrated with vibrancy.